A Case Study of Interactive Teaching in a Listening Session at a Language Institute - Hilma Safitri (Journal of Language Learning and Research (JOLLAR), 2019)
Improving listening skills is one of urgent problems in education. Insufficiency of students’ linguistics and non-linguistics knowledge or background knowledge to comprehend ideas during listening could be solved by providing them with interactive tasks since to learn to listen is to learn to respond and to continue a chain of listening and responding. This study aims to uncover interactive teaching in a listening session at LBPP-LIA Kalimalang Jakarta. The subjects of the study were the students of Intermediate 3 together with their teacher. The object of the study were the aspects covered by classroom interaction: student-student and student-teacher interactions. Data collection consisted of audio-recording of the spoken exchange and note taking of all observed activities during the listening session. As a qualitative study, the findings were described in terms of words. The result showed the teacher seemed to be aware that interactive tasks in pair/group work would benefit the students. The interaction patterns taken place among participants involved in a discussion reflected an interactive teaching. However, the teacher should have developed his roles. He needed to vary his techniques in maintaining the interaction, therefore, the students were motivated to volunteer information, comment, or questions.